PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Pandanaran) - Junistyaningrum, Nurulita; Sugiarto, Yohanes (Faculty of Economics and Business Diponegoro University, 2016)
This research examines two independent variables that is Building Service Partnership–of which the dependent variable of Customer Loyalty can be influenced–and Customer Satisfaction as the interverning variable. The direct coefficient determination (R2) test results 22,7%, meanwhile a 30,0% derived from the indirect coefficient determination (R2) test. In the other hand, testing hypotheses concerning partial correlation confirms that (i) Building Service Partnership indicates a positive and significant relationship towards Customer Satisfaction; (ii) Total Quality Management indicates a positive and significant relationship towards Customer Satisfaction; (iii) Building Service Partnership indicates a positive and significant relationship towards Customer Loyalty; (iv) Total Quality Management indicates a positive and significant relationship towards Customer Loyalty; and (v) Customer Satisfaction indicates a positive and significant relationship towards Customer Loyalty. From the significant hypothesis test (F-test), it can be derived that there is positive and significant influence between Building Service Partnership and Total Quality Management towards Customers Loyalty, with Customer Satisfaction as its interverning variable.